Evaluation of the juice brix of wild sugarcanes (Saccharum spontaneum) indigenous to Japan. (2nd April 2016) - Sakaigaichi, Takeo; Terajima, Yoshifumi; Matsuoka, Makoto; Terauchi, Takayoshi; Hattori, Taiichiro; Ishikawa, Shoko
Abstract: Modern sugarcane cultivars are derived from the interspecific crossing between Saccharum officinarum and wild sugarcane, Saccharum spontaneum . The introgression of valuable characteristics from wild sugarcane is recognized as extremely important, but this process typically requires long-term effort over multiple generations of backcrosses owing to the low sugar content of the initial interspecific hybrids. In this study, we aimed to identify Japanese wild sugarcanes with high juice brix in order to promote effective interspecific crossing of sugarcane. Sixty-four accessions from the Nansei Islands and 70 accessions from the Honshu were evaluated for juice brix. Wild sugarcanes with high juice brix were demonstrated to exist among wild sugarcanes indigenous to the Honshu. A significant difference was observed between the median juice brix values of wild sugarcanes of the Nansei Islands and those of the Honshu. The relationship between juice brix and stem traits was then examined in 20 wild sugarcanes, 10 each from the Nansei Islands and the Honshu. The reproducibility of juice brix value in both experiments was confirmed. In contrast to juice brix, stem traits, such as length, diameter, and volume, were typically smaller in wild sugarcanes from the Honshu. Moreover, a negative correlation was observed between the index of stem volume and juice brix. In this study, we identified outstanding wild sugarcanes with high juice brix. Using germplasms from the identified wild sugarcanes in interspecific crossing could contribute to the increases in both yield and sugar content.